2019
DOI: 10.1017/s0267190519000138
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Digital Discourses: What Can We Learn From Hashtags and Digital Games to Expand Learners’ Second Language Repertoire?

Abstract: In recent years, digital technologies have expanded the possibilities for human interactions in ways that were never before imagined, further complicating the teaching and learning of languages (Taguchi & Sykes, 2013; Thorne, Sauro, & Smith, 2015). Despite this complexity, when approached as meaningful, high-stakes practices, discourses in digital contexts can be highly useful for language learning and teaching. This article synthesizes work related to two digital discourse contexts, specifically hasht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Hashtags are being used by both the demand and supply sides to share information and promote or discuss destination attributes (Shaheer et al, 2018). Trending hashtags can cross cultural boundaries (Sykes, 2019), aiding tourism strategists, managers, and marketers (Gupta and Gupta, 2019) and influencing visitation as the destination image generated online influences travel motivations alongside travel types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hashtags are being used by both the demand and supply sides to share information and promote or discuss destination attributes (Shaheer et al, 2018). Trending hashtags can cross cultural boundaries (Sykes, 2019), aiding tourism strategists, managers, and marketers (Gupta and Gupta, 2019) and influencing visitation as the destination image generated online influences travel motivations alongside travel types.…”
Section: Discussionmentioning
confidence: 99%
“…These hashtags are used as an instrument for sharing content, advancing the popularity of any particular topic (George et al, 2018), and engaging public attention (Mohammadi et al, 2018). Hashtags can also be used to organise and sort tweets and, therefore, abstract the whole message (Sykes, 2019). From July 2009 onwards, Twitter hyperlinked the 'hashtag' word, which enabled the user to access all other tweets which use the same hashtag (Sykes, 2019).…”
Section: Twitter and Hashtagsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four functions that are relevant for this study. Others have put forth groupings into three main functions (e.g., Sykes, 2019) but a slightly more fine grained approach seemed more fruitful here. The first one is supporting visibility and findability (Page, 2012).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Social media and the dynamics of participatory culture present numerous opportunities for designing meaningful language learning experiences (Kessler, 2018b). Researchers have observed that linguistic practices continue to evolve the longer that we are immersed in these digital social spaces, and this results in the need to prepare both teachers and learners for the changing nature of digital discourse in these domains (Sykes, 2019). As we observe how people engage with others and learn informally in these domains, there has been increased interest in identifying the aspects of these informal social spaces that may be adopted to design more engaging learning experiences.…”
Section: Increasing Diversity Of Learning Spacesmentioning
confidence: 99%